THE IMPACT OF SECURITIES-BASED FINANCING ON SMALL AND MEDIUM ENTERPRISES (SMES) DEVELOPMENT - Tirkashev Mirasror Yusup ugli (The Conference Hub, 2025)
This study investigates the influence of securities-based financing on the growth and development of small and medium enterprises (SMEs). Securities-based financing—comprising equity issuance, bonds, and alternative securities such as equity crowdfunding—provides SMEs with non-bank funding sources. The analysis explores how access to capital markets affects SMEs’ performance, sustainability, and innovation capacity. Results reveal that securities financing positively contributes to SME growth, profitability, and market expansion. Policy and practical implications are also discussed.
Keywords: Securities-based financing, Small and Medium Enterprises (SMEs), Capital markets, Equity financing, Debt securities, Equity crowdfunding, Alternative financing instruments, Access to finance, SME development, Financial performance